Is Doping of Spiro-OMeTAD a Requirement for Efficient and Stable Perovskite Indoor Photovoltaics? - Toikkonen, Sami; Grandhi, G. Krishnamurthy; Wang, Shaoyang; Baydin, Bora; Al-Anesi, Basheer; Jagadamma, L. Krishnan; Vivo, Paola (AMER ASSOC ADVANCEMENT SCIENCE, 2024)
Lead halide perovskite (LHP) photovoltaics deliver high voltages even under low-light illumination intensities, thus emerging as a promising indoor photovoltaic (IPV) technology. The doping of the 2,2 ',7,7 '-tetrakis(N,N-di-p-methoxyphenylamino)-9,9 '-spirobifluorene (Spiro-OMeTAD) hole-transport layer (HTL) is the most widely adopted strategy for high-performance LHP-based solar cells. Yet, the importance of Spiro-OMeTAD doping is unclear in the context of indoor photovoltaics. In this report, we examine the role of the traditional Spiro-OMeTAD dopants on the performance of LHP-based IPVs. The diminished influence of the series resistance under indoor lighting leads to an improved fill factor of IPV devices even in the absence of the dopants. The pristine (dopant-free) Spiro-OMeTAD HTL ensures a power conversion efficiency (PCE) as high as 25.6% at 1,000 lux, comparable to that of 29.7% in the presence of the dopants, and an open-circuit voltage of approximate to 0.65 V even at 50 lux. The undoped Spiro-OMeTAD-containing devices exhibit a approximate to 25% gain in their PCE under long-term and continuous white light illumination at the maximum power point, thus leading to the PCE values on par or higher than those of employing doped Spiro-OMeTAD. Furthermore, the current-voltage hysteresis behavior of the undoped Spiro-OMeTAD-containing devices remains unchanged in the 100 to 1,000 lux light-intensity range, unlike the case of doped Spiro-OMeTAD HTL. Our findings suggest that the dopants in Spiro-OMeTAD HTL are not required to achieve efficient, stable, and reliable IPV performance, and the optimization of the various device constituents for outdoor solar cell applications may not necessarily lead to the best performance for indoor photovoltaics.
Keywords: HYSTERESIS; FILMS; Engineering; Instruments & Instrumentation; Optics